Pengembangan Bahan Ajar Audio Berbentuk Rekaman (Audio Record) dalam Pembelajaran PAI - Musyarofah, Siti (Pascasarjana IAIN Lhokseumawe, 2023)
The development of audio-based instructional materials in the form of recordings is a strategic approach to enhancing the quality of Islamic Religious Education (PAI), particularly in cultivating listening competencies and internalizing spiritual values. This conceptual study aims to construct the urgency, characteristics, and development strategies of audio instructional materials within the context of PAI learning. The method employed is library research, using theoretical analysis and literature synthesis. The sources reviewed include books, academic journals, and scholarly documents relevant to instructional media, Islamic educational technology, and audio-based instructional design. The findings indicate that audio media is not merely a supporting tool but a meaningful instructional resource with both pedagogical and spiritual value. Audio recordings offer advantages in stimulating imagination, conveying moral messages reflectively, and systematically training listening skills. The development strategy includes analysing learner needs, formulating learning objectives, preparing scripts, evaluating media, and revising products continuously. The conceptual discussion in this article expands the focus of instructional media studies from visual to auditory domains and proposes a simple yet meaningful approach to Islamic character education. This study contributes to strengthening audio-based instructional design and encourages PAI educators to be more creative in utilizing contextual and value-driven educational technologies.